2014
DOI: 10.1002/14651858.cd007953.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent versus daily therapy for treating tuberculosis in children

Abstract: Intermittent versus daily therapy for treating tuberculosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…A Cochrane review comparing intermittent with daily therapy in children with PTB found no detectable difference between twice-weekly and daily treatment in outcomes, but the data were insufficient to support or refute the use of intermittent treatment over daily treatment in children with tuberculosis. 41 No randomized controlled trials have studied intermittent therapy for extrapulmonary tuberculosis. For extrapulmonary tuberculosis including TBM, daily therapy is recommended in both the intensive and continuation phase.…”
Section: Practical Aspects Of Treatmentmentioning
confidence: 99%
“…A Cochrane review comparing intermittent with daily therapy in children with PTB found no detectable difference between twice-weekly and daily treatment in outcomes, but the data were insufficient to support or refute the use of intermittent treatment over daily treatment in children with tuberculosis. 41 No randomized controlled trials have studied intermittent therapy for extrapulmonary tuberculosis. For extrapulmonary tuberculosis including TBM, daily therapy is recommended in both the intensive and continuation phase.…”
Section: Practical Aspects Of Treatmentmentioning
confidence: 99%
“…Mere DOTS without specific efforts such as transport coupons or food rations does not increase compliance [9]. A publication by Bose et al in the Cochrane Database of Systematic Reviews compared the efficacy and safety of intermittent, short-course anti-TB regimens (twice- or thrice-weekly) with daily short-course anti-TB regimens in treating childhood TB [10]. This review noted that parents of children should be educated regarding the need for adherence and treatment completion and appropriately compensated for trial-related expenses, to ensure continued participation.…”
Section: Introductionmentioning
confidence: 99%
“…The recent Cochrane review comparing daily versus intermittent anti-tuberculosis therapy in children 1 reported that there is no obvious difference between the two treatment regimens. The authors also highlighted the poor quality of individual trials, leading to this result.…”
Section: Introductionmentioning
confidence: 99%
“…This review's conclusion is completely different from that published in a previous systematic review by another group 2 despite examination of the same trials and dataset. 3e6 The main reason for this difference has been explained in the Cochrane review 1 as an error in data extraction (and hence meta-analysis) by the authors of the previous systematic review. 2 In that respect, the Cochrane review 1 is a valuable addition to scientific literature and can be taken as the current best evidence on the subject.…”
Section: Introductionmentioning
confidence: 99%